Analysis of Morning Exercise Activities on Children's Learning Readiness in School - Ivan Hafidz Al Faqih; Tatang Muhtar; Dinar Dinangsit; Anggi Setia Lengkana (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
Learning readiness is an important factor influencing the success of the learning process in elementary school students. Physical activities such as morning gymnastics are believed to improve students’ physical, mental, and emotional readiness to learn. This study aims to analyze the implementation of morning gymnastics and its impact on students’ learning readiness in two elementary schools with different characteristics. The study employed a qualitative approach using a case study method conducted at SD Negeri Selaawi and SD Negeri Sukamaju. Data were collected through observations, interviews, and documentation involving students, teachers, and parents. The findings revealed differences in the frequency, timing, and management of morning gymnastics between the two schools. SD Negeri Selaawi implemented morning gymnastics more routinely and systematically compared to SD Negeri Sukamaju. These differences affected students’ learning readiness, as students who participated consistently in morning gymnastics demonstrated better concentration, improved physical fitness, and more stable emotional conditions. The study concludes that morning gymnastics positively contributes to students’ multidimensional learning readiness, including physical, mental, and emotional aspects. The novelty of this research lies in its comparative analysis of the implementation of morning gymnastics in two different elementary schools, providing a broader understanding of how the intensity and consistency of physical activity programs influence students’ readiness to learn. The findings also emphasize the importance of structured and sustainable physical activity programs in supporting effective learning processes in elementary education.